Financial reporting in tabung masjid management driven by Maqasid Al-Shariah in Malaysia - Mhd. Sarif, Suhaimi; Zakariyah, Luqman; Mohd Noor, Azman (Islamic Cultural Centre & The London Central Mosque, 2018)
Financial reporting is an essential document to reflect the financial strength and capability of organizations. As a public place of worship, mosques or masajid in Malaysia are fully governed by State Religious Departments. Any activity requires written consent from the State Religious Authority including Tabung Masjid. Tabung Masjid Management of mosques is regulated by state religious administration law. Conventional approach is expected which make the idea would will remain as an idea only. The study argues that the compliance approach is necessary at the operations level but not at the corporate level. A case study method on a few selected mosques found that the finance committee has no choice but to abide by the regulation. In the meantime to use innovative way through specific fund raising to address social issues. The study recommends the Tabung Masjid management to be use creative way of increasing the value of the fund within the Shariah compliant spirit.